A Survey to Assess the Effectiveness & Utility of the District Residency Program Implemented for the Resident Doctors (GAIMS Journal of Medical Sciences, 2024)
The District Residency Program (DRP) was one of the novel changes introduced by the National Medical Council (NMC) advocating a community centric objective for the post-graduate medical students. A survey was conducted to study the strengths, weaknesses, opportunities & threats to the program. The residents chiefly complained of the logistics, accommodation & the duration of the program. Despite the early implementation issues amongst other challenges, the program might serve as an important learning module & pave the way forward for improving the health services in the developing countries like India where more than 60% of the population has a limited access to the specialized health care facilities.